After Anna - Scottoline, Lisa (New York : St. Martin's Press, 2018)
"Dr. Noah Alderman, a widower and single father, has remarried a wonderful woman, Maggie Ippolitti, and for the first time in a long time, he and his young son are happy. Despite her longing for the daughter she hasn$1 (Bt seen since she was a baby, Maggie is happy too, and she$1 (Bs even more overjoyed when she unexpectedly gets another chance to be a mother to the child she thought she$1 (Bd lost forever, her only daughter Anna. Maggie and Noah know that having Anna around will change their lives, but they would never have guessed that everything would go wrong, and so quickly. Anna turns out to be a gorgeous seventeen-year-old who balks at living under their rules, though Maggie, ecstatic to have her daughter back, ignores the red flags that hint at the trouble brewing in a once-perfect marriage and home. Events take a heartbreaking turn when Anna is murdered and Noah is accused and tried for the heinous crime. Maggie must face not only the devastation of losing her daughter, but the realization that Anna$1 (Bs murder may have been at the hands of a husband she loves. In the wake of this tragedy, new information drives Maggie to search for the truth, leading her to discover something darker than she could have ever imagined."--s
Keywords: Teenage girls -- Crimes against -- Fiction; Murder -- Fiction; Stepfamilies -- Fiction; Thrillers (Fiction).